2011
DOI: 10.1097/01.aoa.0000400290.87898.c1
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Morbidity in Late Preterm Births

Abstract: Context-Late preterm births (LPTB, 34 0/7-36 6/7 weeks) account for a growing proportion of prematurity-associated short term morbidities, particularly respiratory, that require specialized care and prolonged neonatal hospital stays.Objective-To assess short-term respiratory morbidity in LPTB compared to term births in a contemporary cohort of deliveries in the United States.Design, Setting, and Participants-Retrospective collection of electronic data from 12 institutions (19 hospitals) across the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 2 publications
2
82
0
12
Order By: Relevance
“…Neonates, whether born preterm or early term, are at increased risk for respiratory morbidity, which can include HRF associated with PH [19]. Preterm birth may disrupt normal lung development, resulting in a deficit in pulmonary circulation, decreased surface area for gas exchange, increased vasoreactivity and hypoxic vasoconstriction, which lead to increased pulmonary vascular resistance [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Neonates, whether born preterm or early term, are at increased risk for respiratory morbidity, which can include HRF associated with PH [19]. Preterm birth may disrupt normal lung development, resulting in a deficit in pulmonary circulation, decreased surface area for gas exchange, increased vasoreactivity and hypoxic vasoconstriction, which lead to increased pulmonary vascular resistance [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Late preterm infants have increased morbidities and require disproportionate healthcare resources compared with term infants (2,3). Short term morbidities encountered in late preterm infants include respiratory distress syndrome (RDS), retained lung fluid, sepsis evaluations, temperature instability, hyperbilirubinemia, hypoglycemia, apnea, and poor feeding (4)(5)(6)(7)(8)(9). These morbidities reflect incomplete maturation of multiple organ systems including the central nervous system (CNS) (10).…”
mentioning
confidence: 99%
“…Incidence of respiratory morbidity in our study in the late preterms was 35 %. In studies conducted by Judith et al, Jaiswal et al and Wagh et al [4][5][6], the incidence of respiratory morbidity in the late-preterm group was found to be 9, 10.5 and 29.8 %, respectively. Our study appears to show a higher incidence as we have included babies who had mild RDS lasting for few hours immediately after birth requiring no active intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that late-preterm infants have considerable short-and long-term morbidity and mortality; hence, every attempt must be made to prolong the pregnancy till 36 completed weeks [3,5,13]. Maternal and fetal indications for early delivery should be critically evaluated and risk benefit ratio should be judicially analyzed, keeping in mind the risks of neonatal morbidity.…”
Section: Discussionmentioning
confidence: 99%